Key Concepts of Modern Western Psychological Theory - Sri Haryanto (Yayasan Adra Karima Hubbi, 2024)
Background. Modern Western psychology developed by focusing on observing and understanding human behavior through scientific methods. Psychoanalysis developed by Sigmund Freud, who tried to understand how unconscious factors influence human behavior and thoughts. Purpose. basic theory of psychoanalysis emphasizes the importance of understanding unconscious conflicts, complexes, and defense mechanisms in shaping one's personality and behavior. Method. Behavioristic psychology emphasizes the importance of stimulus and response in shaping behavior. Behaviorism emphasizes the importance of learning through stimulus and response, as well as the process of association between stimulus and response that forms patterns of behavior. Results. Humanistic psychology includes concepts of self-awareness, taking responsibility for life choices, and the desire for self-actualization. Transpersonal psychology recognizes that humans have spiritual needs and potentials that encompass experiences beyond the material and ego aspects. The main idea in transpersonal psychology involves integrating spiritual aspects or experiences that transcend personality (transpersonal). Conclusion. Understanding the main points of psychoanalytic, behavioristic, humanistic and transpersonal thought as schools of modern western psychology will provide a comprehensive understanding of modern western psychology.